Ethnomathematics-Based Missouri Mathematics Project Learning Model to Improve Learning Process and Achievements - Zaid Zainal; Irmayani Irmayani; Wawan Krismanto (PT. Pusmedia Group Indonesia, 2025)
This study aims to determine the improvement of the learning process and achievement of students by implementing the ethnomathematics-based Missouri Mathematics Project (MMP) learning model. This research is a class action research with two cycles. The subjects in this study were teachers and students of grade 5 of SDN 35 Barru, South Sulawesi, Indonesia, consisting of a teacher, six male students, and six female students. The data collection techniques used are observation, tests, and documentation. The data analysis techniques used are data condensation, data presentation and conclusion drawing, which are processed qualitatively. The results of this study show that in cycle I, the learning process in the activities of teachers and students is at a sufficient qualification, which can be seen from the enthusiasm of students when participating in learning because what is learned is close to their lives. Besides that, it also appears that when students observe Bugis cultural objects, students look enthusiastic about learning. In contrast, student learning achievement are just at sufficient qualifications. In cycle II, there was an increase; the results of the study showed that the learning process in the activities of teachers and students was at good qualifications; it can be seen that the learning activities became more fun so that students could more easily understand the material, and the group discussion process became more active, while the student learning achievements were also at good qualifications. Thus, the mathematics learning process and achievement can be improved by implementing the ethnomathematics-based MMP learning model.